Table of Content - - (Journal of Educational and Psychological Sciences, 2023)
Table of Content: 1. The degree of impact of the admission policies of Jordanian public universities in aligning their outputs with the requirements of the labor market from the point of view of the faculty Dr. Nisreen Abd Alhafed Alofishat 2. Reality of remote Training in light of the Corona pandemic from the male and female teacher’s point of view at Riyadh and Dammam Dr. Abdullah Mohmmad Al-Shaye, Mrs. Afnan Ali Mohmmad Al-Wadey 3. Parental treatment methods and their relationship to achievement motivation among a sample of gifted female students at the secondary stage in Jeddah Mrs. Maram Hajjaj Al- Mabadi, Dr. Manal Yahya BaAmer 4. Methods of access for people with intellectual disabilities to public education curricula and the factors affecting them from the point of view of teachers in Al-Jouf region Mrs. May Farzal Alshammari, Dr. Maha Saud Albulayhid 5. Emotional Eating- Theoretical Framework Mrs. Rasha Mohammed Alshehri, Prof. Sabah Alrefae, Asst-Prof. Arwa Alkhalaf 6. Islamic texts refer to psychosomatic illnesses Historical comparison Mr. Faisal Qasem Aloshari